Extremely low dose 18F-FDG PET imaging and its potential use for lung cancer screening - Yan, Jianhua; Wu, Zhifang; Li, Sijin (Translational Cancer Research, 2017)
Lung cancer is the most common cause of death among both men and women from cancer worldwide. Overall, less than 20% of patients with lung cancer are still alive 5 years after diagnosis (1) although there are significant improvements of treatment. The low survival rate could most likely be due to the low early detection. Most lung cancers are first diagnosed based on symptoms and regular chest X-rays.